Experimentally exploring nano-fluid of alumina nano-particles enriched waste coconut oil effects in cutting zone temperature reduction in motor shaft manufacturing process. (2022) - Anbuchezhiyan, G; Saravanan, R; Pugazhenthi, R.; Rathinam, V.; Nagireddy, Madhavi
Highlights: This research investigated clean machining possibilities with use of Novel Nano fluid. Graphite enriched waste coconut oil based reduced the Cutting zone temperature. Molybdenum disulphide Nano-particles reduces the Cutting zone temperature by 27.36%. Proposed clean manufacturing reduced the Cutting zone temperature significantly. Abstract: Metal cutting, in general, produces heat, which has an impact on the machining quality of the final job. The surface quality of the shaft is a major factor in fatigue stress shaft failures. Coconut oil or leftover coconut oil from Kerala chips was utilized here. shop The cutting zone temperature response is utilized to optimize the metal removal process's parameters. The cutting speed was changed from 40 to 190 m/min, the tool feed rate was varied from 0.05 to 0.20 mm/rev, and the CVD coated tool was employed with four different nose radius 0.3 mm, 0.6 mm, 0.9 mm, and 1.2 mm, and an L16 orthogonal array was used to generate the minimal experimental combinations. The results were compared to current dry machining procedures. According to the results of the experimental investigation, the proposed Alumina Nanoparticles enriched waste coconut oil based wet machining method reduces the Cutting zone temperature by 27.36 percent on average and ensures that the results do not violate the statistical assumption, it can be recommended for processing SAE 1045 material for shaft manufacturing.